Characteristics of mid‐level clouds over West Africa. (6th February 2018) - Bourgeois, Elsa; Bouniol, Dominique; Couvreux, Fleur; Guichard, Françoise; Marsham, John H.; Garcia‐Carreras, Luis; Birch, Cathryn E.; Parker, Douglas J.
Abstract : Mid‐level clouds, located between 2 and 9 km height, are ubiquitous in the tropical belt. However, few studies have documented their characteristics and tried to identify the associated thermodynamic properties, particularly in West Africa. This region is characterized by a strong seasonality with precipitation occurring in the Sahel from June to September (monsoon season). This period also coincides with the annual maximum of the cloud cover. Here, we document the macro‐ and microphysical properties of mid‐level clouds, the environment in which such clouds occur, as well as their radiative properties across West Africa. To do so, we combined high‐resolution observations from two ground‐based sites (including lidar and cloud radar) in contrasted environments: one in the Sahel (Niamey, AMMA campaign, 2006) and the other in the Sahara (Bordj Badji Mokhtar, Fennec campaign, June 2011) along with the merged CloudSat‐CALIPSO satellite products. The results show that mid‐level clouds are found throughout the year with a predominance around the monsoon season early in the morning. They also are preferentially observed in the southern and western parts of West Africa. They are usually thin (most of them are less than 1000 m deep) and as observed in Niamey, mainly composed of liquid water. A clustering method applied to Niamey data allows us to distinguish three different types of cloud: one with low bases, one with high bases and another with large thicknesses. The two first cloud families are capped by an inversion. The last family is associated with a large vertical moisture transport and likely has the highest radiative effect at the Earth's surface among the three cloud types. Abstract : This article gathers several sources of observations of mid‐level clouds in West Africa in order to document the frequency of occurrence, diurnal cycle, macro‐ and microphysical properties, thermodynamic environments and radiative impacts of mid‐level clouds. One unique feature of our study is to combine high‐resolution observational data from two ground sites (Niamey and Bordj Badji Mokhtar) with merged CALIPSO‐CloudSat satellite products to provide a better knowledge and understanding of these cloud processes over West Africa.